Cultural Competency in the Primary Health Care Relationship - Ferreyra Galliani, Mariella (Université d'Ottawa / University of Ottawa, 2012)
Cultural competency is theorized as the sensitivity of practitioners from the dominant culture towards the diverse cultural backgrounds of their patients. Less attention is placed on how communication between providers and patients can enable patients to share their health care beliefs. An evidence review of the literature around the conceptualization of cultural competency in health care was performed, and interviews were conducted aiming to understand what immigrant patients perceive as culturally competent care and its effect on the relationship between them and their providers. Definitions of cultural competence varied, and no conclusive studies linking cultural competence to improved health outcomes were found. Findings from the participant interviews helped to address gaps in the literature by confirming a preference for a patient-centred approach to culturally competent care, in addition to identifying pre-existing expectations for the health care encounter and patient-dependent factors as additional elements influencing the physician-patient relationship.
Keywords: Cultural competency; Immigrant health; Patient-centredness; Cross-cultural communication; Qualitative methods